2023
DOI: 10.1088/1475-7516/2023/03/060
|View full text |Cite
|
Sign up to set email alerts
|

Ghost and Laplacian instabilities in teleparallel Horndeski gravity

Abstract: Teleparallel geometry offers a platform on which to build up theories of gravity where torsion rather than curvature mediates gravitational interaction. The teleparallel analogue of Horndeski gravity is an approach to teleparallel geometry where scalar-tensor theories are considered in this torsional framework. Teleparallel gravity is based on the tetrad formalism. This turns out to result in a more general formalism of Horndeski gravity. In other words, the class of teleparallel Horndeski gravity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…There has also been initial work on the stability of the theory with a particular focus on theoretical conditions that can be derived from Minkowski space as described ref. [58]. It is thus critical to analyse in a concrete way the full cosmology of this new teleparallel analogue of Horndeski gravity.…”
Section: Jcap08(2023)074mentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been initial work on the stability of the theory with a particular focus on theoretical conditions that can be derived from Minkowski space as described ref. [58]. It is thus critical to analyse in a concrete way the full cosmology of this new teleparallel analogue of Horndeski gravity.…”
Section: Jcap08(2023)074mentioning
confidence: 99%
“…where capital Latin indices indicate components at the Lorentz spacetime, while small ones, the associated 3 dimensional spatial part. For greater details one can check [30,58].…”
Section: Jcap08(2023)074mentioning
confidence: 99%
“…Besides a handful of special assumptions to avoid the instabilities in Horndeski theory such as "asymptotically strong gravity" or very specific models [11,[15][16][17], the alternative of Horndeski theory on spacetimes with torsion has been recently analyzed in [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In particular, it has been shown that in Horndeski-Cartan gravity (considering torsion in the second order, metric formalism), a similar No-Go theorem also holds (in up to the quartic case ) [19]: namely, the alltime sub/luminality, stability and nonsingularity of an spatially flat FLRW cosmology are mutually inconsistent, up to a few special cases.…”
Section: Introductionmentioning
confidence: 99%
“…This amounts to introduce torsion in the second order formalism, because the equations for the metric remain of second order. Other approaches in the context of Horndeski have been recently analyzed in[20][21][22][23][24][25][26][27][28][29][30][31][32][33] …”
mentioning
confidence: 99%